(untitled) (AYUSHDHARA, 2023)
In order to analyze the potential bioactive constituents of leaf extracts of Prosopis Cineraria/ Khejri- National tree of Rajasthan, a plant with enormous Ayurvedic properties, Fourier Transform Infrared Spectroscopy (FTIR) along with Ultra Violet Spectroscopy (UV) and added Field Emission Scanning Emission Microscope with Energy Dispersive X-ray analysis (FESEM-EDAX) were carried out. The authors too demonstrated cell line studies via MTT Assay for MOLT 4, blood cancer in different concentrations and found Khejri as toxic with validated IC50. Further, Gas Chromatography-Mass Spectroscopy (GC-MS) and High-Performance Liquid Chromatography (HPLC) were tested and certain compounds gave spectrum with few major peaks concluded by other results, most of which are bioactive compounds which may act as antimicrobial, anti-cancerous, antioxidant, antiviral and anti-inflammatory agents. On an all, Khejri/Sami leaves of Mimosaceae family of Spunge tree is having anti cancerous properties for blood cancer that may repair punctured blood vessels if being treated properly. The authors have demonstrated the testing over country eggs with treated/ untreated group of eggs and found the formation of blood vessels that gesture how effective the drug is, being composed of Khejri extract. It is not only confined to cancer diseases but acts as a very good agent for inflammation, digestion and conjunctivitis. On an all, this natural compound so extracted is found to be useful for blood cancer with IC50 as 57.11 that simply reflect that the medicine composed from the same will be highly beneficial for cancer patients - let it be Ayurvedic, homoeopathic or allopathic.